Beneficial microbes in a changing environment: are they always helping plants to deal with insects?. (11th February 2013) - Pineda, Ana; Dicke, Marcel; Pieterse, Corné M.J.; Pozo, María J.; Biere, Arjen
Summary Plants have a complex immune system that defends them against attackers (e.g. herbivores and microbial pathogens) but that also regulates the interactions with mutualistic organisms (e.g. mycorrhizal fungi and plant growth‐promoting rhizobacteria). Plants have to respond to multiple environmental challenges, so they need to integrate both signals associated with biotic and abiotic stresses in the most appropriate response to survive. Beneficial microbes such as rhizobacteria and mycorrhizal fungi can help plants to 'deal' with pathogens and herbivorous insects as well as to tolerate abiotic stress. Therefore, beneficial microbes may play an important role in a changing environment, where abiotic and biotic stresses on plants are expected to increase. The effects of beneficial microbes on herbivores are highly context‐dependent, but little is known on what is driving such dependency. Recent evidence shows that abiotic stresses such as changes in soil nutrients, drought and salt stress, as well as ozone can modify the outcome of plant–microbe–insect interactions. Here, we review how abiotic stress can affect plant–microbe, plant–insect and plant–microbe–insect interactions, and the role of the network of plant signal‐transduction pathways in regulating such interactions. Most of the studies on the effects of abiotic stress on plant–microbe–insect interactions show that the effects of microbes on herbivores (positive or negative) are strengthened under stressful conditions. We propose that, at least in part, this is due to the crosstalk of the different plant signalling pathways triggered by each stress individually. By understanding the cross‐regulation mechanisms we may be able to predict the possible outcomes of plant‐microbe–insect interactions under particular abiotic stress conditions. We also propose that microbes can help plants to deal with insects mainly under conditions that compromise efficient activation of plant defences. In the context of global change, it is crucial to understand how abiotic stresses will affect species interactions, especially those interactions that are beneficial for plants. The final aim of this review is to stimulate studies unravelling when these 'beneficial' microbes really benefit a plant.